THE EFFECT OF THE COLLAPSE OF THE TSARDOM EMPIRE AND THE ATTITUDE OF THE TEMPORAL RUSSIAN BOURGEOIS GOVERNMENT TOWARDS THE POLISH CASE (FEBRUARY-NOVEMBER, 1917( - Safanah Maan Abdel Kareem; Wisam Ali Thabet (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The fall of the tsarist regime at the hands of the provisional bourgeois government in March 1917 had tangible results in the nature of the Soviet policy towards the return of Poland, as a sovereign state after its weakness, which resulted in political and military conflicts to draw a new political map, which affected the Soviet policy towards Poland regarding The disputed areas include the originally Polish areas and the Russian-majority areas claimed by Poland, and therefore the Soviet-Polish conflicts occurred, which led to the intervention of the major powers and standing by Poland, which was part of the barrier of international isolation against Russia, and it benefited a lot from those countries to stand In the face of the Soviet threat, and the realization of its various demands.